Remote thermal activation of particles for component release and activation
Matrix particles with susceptor elements and releasable components enable efficient, localized polymerization in opaque materials, overcoming the limitations of global heating by allowing precise control and reducing energy consumption and equipment complexity.
Patent Information
- Application Number
- JP2024528485
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-11
- Filing Date
- 2022-11-14
- Publication Date
- 2025-01-22
AI Technical Summary
Existing methods for polymerization in composite materials are limited by global heating, which requires complex equipment, high energy consumption, and is inefficient for opaque substrates, especially those with glass transition temperatures below room temperature, and lack precise control over reaction initiation.
Matrix particles comprising a matrix material, a susceptor element, and a releasable component that can be thermally activated via electromagnetic radiation, allowing for localized and remote activation of chemical reactions without bulk heating.
Enables efficient, localized, and controlled polymerization in opaque materials, reducing energy consumption and equipment complexity, and allowing for faster reaction initiation and uniform mixing of fillers, even in thick substrates.
Smart Images

Figure 2025501442000001_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims the benefit of U.S. Provisional Application No. 63 / 278,235, filed November 11, 2021, which is incorporated herein by reference in its entirety. [Technical field]
[0002] The present invention relates to a matrix particle, comprising (i) a matrix material, (ii) at least one susceptor element, and (iii) at least one releasable component, said matrix material being capable of fully or partially changing its physical or chemical properties; said at least one susceptor element being incorporated into said matrix material; said at least one releasable component being capable of affecting a chemical reaction and being incorporated into said matrix material; said at least one susceptor element being thermally activatable via radio frequency or microwave radiation. The present invention also relates to remote thermal activation or heating of such susceptor elements within the matrix material, whereby the releasable component in proximity to the susceptor element is released away from or in proximity to the matrix material and activated to perform its function, e.g. carry out a chemical reaction, such as polymerization. The present invention also relates to the preparation of such matrix particles. [Background technology]
[0003] In composite manufacturing, the elimination of total heating results in higher throughput and eliminates the need to cool parts of the equipment or the molding material before it is removed from the mold. Recently, two components can be mixed to form a reactive system and polymerization can be initiated by activating a catalyst with light or by total heating of the composition or the like. Each method has inherent limitations. Total heating requires long times, uses the greatest amount of energy and associated complex equipment, and has limited performance due to excess material caused by internal stresses due to polymerization through heating and cooling. Total heating cannot be used for bonding applications of elastomeric substrates that have glass transition temperatures below room temperature. The mixing of the two components can be the same or more complex, requiring complex mixing or measuring equipment to achieve uniform cure and proper mixing ratios of each. Originally, light was limited to transparent objects and could only cure thinner objects, and required special vessels to avoid light, excessive catalyst loadings, usually greater than 1%, and usually excessive heat energy input, again requiring complex equipment. On the other hand, activating catalysts and co-catalysts incorporated into the matrix particles improve product life. For example, in B-stage products such as thermosetting prepregs and film adhesives, the product is refrigerated until use to improve life and pot life.
[0004] In composite manufacturing, the elimination of overall heating helps achieve higher throughput by eliminating the need for a cooling step before demolding the elements from the mold.
[0005] In industrial manufacturing or processing, it is desirable to avoid the use of total heating, to cure larger objects as needed as with light, to avoid complex curing equipment, to avoid the need for complex metal-based molding equipment, and to minimize the amount of catalyst, such as the limited pot life (or pot life) of two-component or two-part systems.
[0006] In bonding, overall heating limits the use of thicker substrates with higher glass transition temperatures. Higher molecular weight materials are an obstacle to accepting higher loadings of fillers or reinforcing agents, such as ground carbon and glass fibers. By using low molecular weight materials, higher filler contents can be used. Uniform mixing of fillers and high performance without rheological issues are advantages of using low molecular weight materials.
[0007] Chemical activation through opaque objects is often limited as discussed above, unless the object is sufficiently transparent to substantially transmit light. Techniques are needed that can penetrate opaque materials, especially over substantial distances. This would provide new capabilities, allowing polymerization to be initiated in objects filled to various degrees with a variety of fillers, possibly without the need for heat and without the limitations of light transmission.
[0008] As with current technology, the release of components in a chemical reaction must be triggered by the environment outside the chemical reaction chamber, as opposed to events occurring from inside the particle, which is similar to bulk heating, or, if using external light, is limited by thinness.
[0009] Overall, there is a need to activate chemicals and achieve the required activation without overall heating, minimal energy use, minimal materials, and minimal catalyst use, achieve the desired fast chemistry, minimize the complexity, cost and space of the equipment, and minimize or eliminate invasive procedures. Summary of the Invention
[0010] In one embodiment, the present invention relates to a matrix particle comprising: (i) a matrix material; (ii) at least one susceptor element; and (iii) at least one releasable and / or activatable component incorporated in the matrix material and adjacent to the susceptor element, wherein the matrix is capable of fully or partially changing its physical properties, the at least one susceptor element is incorporated in the matrix material, the at least one susceptor element is capable of being thermally activated via electromagnetic radiation, and the at least one releasable and / or activatable component is capable of affecting a chemical reaction.
[0011] In another embodiment, the present invention relates to a matrix particle as described above, comprising one or more matrices incorporated into discrete regions, the discrete regions being one or more shapes, the discrete regions comprising coatings or various layers, each region comprising from about zero to more susceptors and / or releasable components, and the matrix particle as a whole comprising at least one region comprising a susceptor and at least one region comprising a releasable component.
[0012] In yet another embodiment, the present invention relates to a matrix particle as described above, wherein the matrix particle is derived from and / or comprises an organic, inorganic, monomeric, oligomeric, polymeric material, or a combination thereof.
[0013] In another embodiment, the present invention relates to the matrix particle as described above, wherein the at least one susceptor is selected from the group consisting of fullerene compounds, graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, carbon nanotubes, doped carbon nanotubes, carbon sheets, one or more iron metals, one or more oxides of iron metals, superparamagnetic iron oxides (SPIONs), one or more non-ferrous metals, one or more oxides of non-ferrous metals, transition metals, transition metal oxides, silicon carbide based materials, boron nitride, and one or more combinations thereof.
[0014] In yet another embodiment, the present invention relates to the aforementioned matrix particle, wherein the size (or dimension) of the susceptor is in the range of about 0.1 nm to about 1000 μm.
[0015] In one embodiment, the present invention relates to a matrix particle as described above, wherein the susceptor comprises a functionalized susceptor, a non-functionalized susceptor, or both functionalized and non-functionalized susceptors.
[0016] In another embodiment, the present invention relates to a matrix particle as described above, wherein the susceptor is present at the geometric center of a matrix material that is in direct or indirect contact with the susceptor.
[0017] In yet another embodiment, the present invention relates to a matrix particle as described above, wherein the susceptor and / or the releasable component are present in an outer layer of the matrix particle, and the susceptor and the releasable component are in direct or indirect contact.
[0018] In one embodiment, the present invention relates to a matrix particle as described above, which is partially or totally coated with one or more layers of a deformable material.
[0019] In another embodiment, the present invention relates to a matrix particle as described above, wherein the matrix particle is partially or totally coated with one or more layers of a deformable material, the one or more layers comprising a susceptor and / or a releasable component.
[0020] In yet another embodiment, the present invention relates to a matrix particle as described above, wherein the matrix material does not include a susceptor or a releasable component.
[0021] In one embodiment, the present invention relates to a matrix particle as described above, wherein the at least one releasable and / or activatable component is a single chemical, a combination of chemicals, an organic chemical, and / or an inorganic chemical.
[0022] In another embodiment, the present invention relates to the aforementioned matrix particle, wherein the chemical component comprises one or more catalysts, cocatalysts, co-reactants, oxidizers, reaction inhibitor compounds, accelerators, fuels, explosives, or one or more combinations thereof.
[0023] In yet another embodiment, the present invention relates to a matrix particle as described above, wherein the releasable component is released when the matrix deforms, dissolves, melts, expands, shrinks, ruptures, plasticizes, solvates, or combinations thereof.
[0024] In one embodiment, the present invention relates to the aforementioned matrix particle, wherein the frequency of the electromagnetic radiation is in the range of about 300 MHz to about 300 GHz.
[0025] In another embodiment, the present invention relates to the aforementioned matrix particle, wherein the frequency of the electromagnetic radiation is in the range of about 915 MHz to about 2450 MHz.
[0026] In yet another embodiment, the present invention relates to the matrix particles as described above, wherein the frequency of the electromagnetic radiation is in the range of about 915 MHz to about 2450 MHz and / or the power is in the range of 1 to 10000 W.
[0027] In another embodiment, the present invention relates to a matrix particle as described above, wherein the matrix particle is exposed to electromagnetic radiation of the above mentioned frequencies for a period of 10 seconds to 60 minutes.
[0028] In one embodiment, the present invention relates to a matrix particle as described above, the matrix being optionally supported on a support comprising a metal, ceramic, or glass.
[0029] In another embodiment, the present invention relates to a matrix particle as described above, wherein the particle is further chemically surface modified, optionally via one or more chemical reactions comprising a releasable moiety, optionally followed by the formation of a partial or total coating.
[0030] In yet another embodiment, the present invention relates to matrix particles as described above, which have chemical functionality.
[0031] In one embodiment, the present invention relates to a matrix particle as described above, wherein the releasable component comprises a chemically functional monomer, the matrix material comprises a polymeric material, and optionally the matrix particle is coated with a polymeric coating.
[0032] In another embodiment, the present invention relates to a method for preparing the matrix particles described above, the method comprising the steps of: (i) emulsion, dispersion and / or suspension polymerization, or (ii) Core-shell polymerization The process includes the steps of:
[0033] In yet another embodiment, the present invention relates to a method for preparing the matrix particles described above, the method comprising the steps of: (i) coating polymeric microparticles with a material comprising a susceptor and a releasable component; (ii) encapsulating the microparticles incorporating the susceptor and the releasable component with a monomeric, oligomeric or polymeric material; (iii) fusing the susceptor and the releasable component; and / or (iv) incorporating the susceptor and releasable components within the internal pores of the core or the external pores on the surface of porous microspheres.
[0034] In one embodiment, the present invention relates to a method for preparing the matrix particles described above, comprising a copolymerizing step, wherein the copolymerizing step comprises emulsion polymerization, dispersion polymerization, suspension polymerization, or a combination thereof.
[0035] In one embodiment, the present invention relates to a method for affecting a chemical reaction, comprising: (i) providing a bulk reaction mixture; (ii) providing matrix particles as described above; and (iii) Incorporation of matrix particles into the bulk reaction mixture The present invention comprises:
[0036] In another embodiment, the present invention relates to a method of affecting a chemical reaction as described above, comprising: (iv) further comprising impacting the bulk reaction mixture at least once with RF radiation of at least one frequency, and / or MW radiation of at least one frequency to thermally activate the susceptor elements embedded within the matrix particles.
[0037] In yet another embodiment, the present invention relates to a method of influencing a chemical reaction as described above, wherein the influencing with RF radiation of at least one frequency and / or MW radiation of at least one frequency is performed periodically, the period being regular or irregular.
[0038] In one embodiment, the present invention relates to a method of influencing a chemical reaction as described above, wherein the electromagnetic radiation comprises a wavelength in the range of about 1 m to 1 mm and a frequency in the range between 50 MHz and 30 GHz.
[0039] In another embodiment, the present invention relates to a method of affecting a chemical reaction as described above, wherein the frequency of the electromagnetic radiation is within the range of about 915 MHz to about 2450 MHz.
[0040] In yet another embodiment, the present invention relates to a method of affecting a chemical reaction as described above, wherein the frequency of the electromagnetic radiation is in the range of about 915 MHz to about 2450 MHz and / or the power is in the range of 1 to 10,000 W.
[0041] In one embodiment, the present invention relates to a method for affecting a chemical reaction as described above, wherein the reaction is a polymerization reaction.
[0042] In another embodiment, the present invention relates to a method for releasing a releasable component from a matrix particle as described above, comprising the steps of: (a) dispersing matrix particles in a bulk reaction mixture; and (b) impacting the bulk reaction mixture at least once with RF radiation of at least one frequency and / or MW radiation of at least one frequency to thermally activate the susceptor elements embedded within the matrix particles. The present invention comprises:
[0043] In yet another embodiment, the present invention relates to the matrix particle as described above, wherein the one or more variable matrix materials comprise a wax, one or more polymethylmethacrylates (PMMA), styrene, or one or more polymers or copolymers thereof.
[0044] In one embodiment, the present invention relates to a matrix particle as described above, wherein the at least one releasable chemical moiety comprises an activator or catalyst.
[0045] In another embodiment, the present invention relates to the aforementioned matrix particle, wherein the catalyst comprises one or more of Cu-acetylacetone, Cu-2-ethylhexanoate, ferrocene, dimethylaminomethylferrocene, or one or more combinations thereof.
[0046] In yet another embodiment, the invention relates to articles prepared using the above-described methods.
[0047] In yet another embodiment, the present invention relates to an article prepared using the method described above, comprising, in whole or in part: (i) a polymerizable composition or several polymerizable compositions having at least one chemical property; (ii) Reinforced composite articles; (iii) Laminated articles; (iv) Rigid / laminated articles; (v) flexible laminate articles; (vi) a foam; or (vii) any combination thereof It is.
[0048] In one embodiment, the present invention relates to a composition comprising the matrix particles described above, the composition being in whole or in part an adhesive, sealant, coating, paint, ink, plastic, molded plastic, thermoset plastic, molded thermoset plastic, or other polymer-forming composition.
[0049] In another embodiment, the present invention relates to a matrix particle as described above, wherein the releasable and / or activatable component is a catalyst selected from the group consisting of transition metal complexes; transition metal alkoxides; stannous (II) bis(2-ethylhexanoate); carboxylates, alkoxides and complexes of tin, bismuth, zinc, titanium; blocked superacids; dodecylbenzenesulfonic acid; dinonylnaphthalenesulfonic acid; N,N',N'',-tris(dimethylaminopropyl)hexahydrotriazine; organic bases; 1,8-diazabicyclo[5.4.0]undec-7-ene; 1,5-diazabicyclo[4.3.0]nonene-5; (1,4-diazabicyclo2.2.2octane); and combinations thereof. [Brief description of the drawings]
[0050] [Figure 1] FIG. 1 shows a schematic diagram of the method of the present invention.
[0051] [Figure 2A] FIG. 2A shows a currently utilized reaction injection molding process. [Figure 2B] FIG. 2B illustrates the methodology simplified by the present invention.
[0052] [Figure 3A] Figure 3A shows a film lamination adhesive currently available. [Figure 3B] FIG. 3B illustrates the methodology that is simplified as a result of the present invention.
[0053] [Figure 4] FIG. 4 shows an exemplary general structure of the matrix and coating matrix of the invention contemplated herein.
[0054] [Figure 5A] FIG. 5A shows an exemplary compositional structure of the matrix of the present invention contemplated herein. [Figure 5B] FIG. 5B shows an exemplary compositional structure of the matrix of the present invention contemplated herein.
[0055] [Figure 6] 6 shows exemplary matrices and coated matrices of the invention contemplated herein. The matrices can be coated onto objects or disposed in coatings on a variety of objects.
[0056] [Figure 7] FIG. 7 shows a scanning electron microscope (SEM) image of an exemplary hollow particle.
[0057] [Figure 8] FIG. 8 shows an SEM image of an exemplary hollow particle+SPIONs+copper.
[0058] [Figure 9] FIG. 9 shows an SEM image of a commercial PMMA (MX500-ML, Soken) coated with carbon nanotubes (CNTs).
[0059] [Figure 10] FIG. 10 is a graph of a heating curve using a carbon nanostructure (CNS) susceptor.
[0060] [Figure 11] FIG. 11 is a schematic diagram showing the selective placement of susceptors in the shell of a particle of the present invention.
[0061] [Figure 12] FIG. 12 is a schematic diagram showing sheets formed through non-covalent interactions.
[0062] [Figure 13]FIG. 13 is a schematic diagram of functionalized CNTs disposed in the shell of a particle of the present invention.
[0063] [Figure 14] FIG. 14 is a schematic diagram showing the post-functionalization of microparticles to chelate catalysts.
[0064] [Figure 15] FIG. 15 is a schematic diagram showing the capture of CNTs and susceptors using micellar microparticles.
[0065] [Figure 16] FIG. 16 is a schematic diagram showing the entrapment of catalysts with microparticles and CNTs within micelles.
[0066] [Figure 17] FIG. 17 is a schematic diagram of catalyst chelating and susceptor entrapment using micellar microparticles.
[0067] [Figure 18] FIG. 18 shows core-shell particles produced using a commercially available water-based emulsion. Detailed Description of the Invention
[0068] Generally speaking, the present invention relates to a matrix particle comprising (i) a matrix material, (ii) at least one susceptor element, and (iii) optionally at least one releasable component incorporated into the matrix material, where the matrix material can fully or partially change its physical and / or chemical properties; at least one of the susceptor elements is incorporated into the matrix material; and the at least one releasable component can affect a chemical reaction; and the at least one susceptor element can be thermally activated via RF or MW radiation.
[0069] In another embodiment, the matrix particles described above are incorporated or dispersed in a chemical reaction mixture containing constituent reactants likely to undergo a chemical reaction (e.g., in monomers or oligomers in a polymerization reaction). In a further embodiment of the invention, the chemical reaction mixture with dispersed matrix particles is irradiated with radio frequency electromagnetic radiation or microwave radiation. The EMR (electromagnetic radiation) heats the susceptor elements within the matrix particles. This heating then liberates active components, which then catalyze the reaction in the reaction mixture. Thus, the reaction is initiated only when the RF or MW radiation liberates the components from the matrix particles.
[0070] definition
[0071] By "alterable matrix" or "altering matrix" is meant that the matrix material within the matrix particles can be fully or partially deformed, dissolved, melted, expanded, contracted, ruptured, plasticized, or solvated, in other words, can change its physical and / or chemical form to release the active ingredient.
[0072] By "susceptor" is meant particles within a matrix particle that are transformed to be heated or thermally activated by electromagnetic radiation, specifically radio frequency and / or microwave.
[0073] By "affecting a chemical reaction" it is meant that the releasable component is capable of activating or triggering, catalyzing, cocatalyzing, promoting, accelerating, coaccelerating, inhibiting, and / or heating a chemical reaction.
[0074] "Matrix material" or "matrix" refers to the substrate in which the susceptor elements and / or releasable and / or activatable components are incorporated in a matrix particle. The substrate can be, for example, monomeric, oligomeric or polymeric, or inorganic.
[0075] By "incorporated" it is meant that the susceptor or releasable and / or activatable component is in intimate or associated contact with the matrix, e.g., encapsulated or entrapped within the matrix material, e.g., in the pores of the matrix, or bound to one or more matrix materials (which may be within the matrix or on one or more surfaces of the matrix material, and may be fully encapsulated within the matrix material), or partially embedded within the matrix particle by physical bonding, or partially protruding at the surface of the encapsulating matrix particle.
[0076] By "matrix particles" is meant nano- or microparticles (particulates) comprising a matrix material, a susceptor element, and a releasable and / or activatable component, which are used for thermal activation of a bulk reaction mixture as described herein.
[0077] "EM" means high frequency electromagnetic radiation such as radio waves (RF) or microwaves (MW).
[0078] By "releasable and / or activatable component" is meant a component contained in the matrix particulate that plays a role in influencing a chemical reaction in the remote thermal activation of a susceptor in the matrix particle, which then releases or activates the releasable and / or activatable component. As an alternative to the term "releasable and / or activatable component", the terms "active ingredient" or "releasable ingredient" are used. In other words, an active ingredient has not only an activating property but also a releasing property. An active ingredient is in many embodiments a chemical component that has activity, as described below.
[0079] "Bulk reaction mixture" refers to a reaction mixture that can be influenced by matrix particles in releasing the active ingredient. In the bulk reaction mixture, the matrix particles are dispersed and then release the active ingredient by remote activation of the susceptor (e.g., catalyzing the bulk reaction mixture). By way of example, the bulk reaction mixture can be pre-polymerized material and even post-polymerized material to increase molecular weight (e.g., any other chemical reaction such as organic or inorganic or organic-inorganic hybrid reactions). The bulk reaction mixture can be transparent, translucent, or opaque. Or, the bulk reaction mixture can change its transparency as the reaction proceeds.
[0080] In another embodiment, the present invention relates to a method of incorporating matrix particles into a chemical reaction mixture to affect a chemical reaction. For example, the matrix particles may be dispersed in a monomer mixture prior to polymerization. In another embodiment, the present invention relates to activating a chemical reaction, e.g., a polymerization reaction, by heating susceptors in the matrix particles by radio frequency (RF) or high frequency electromagnetic radiation (EMR), such as microwave radiation, which then releases or activates releasable and / or activatable moieties.
[0081] The present disclosure relates to materials and methods for carrying out chemical reactions (e.g., polymerization reactions) that uniformly and optionally activate chemical events. The reactions contemplated by the present invention can be carried out without the need for heating the entire mass of reactants, without optical limitations such as infrared, ultraviolet, or visible light transparency in the case of highly filled materials, opaque materials, etc.
[0082] In some embodiments, the present invention relates to materials and methods for polymerization without the need to mix two reactive components, and in some embodiments, the ability to mix two components but not have an immediate or accelerated reaction and / or have a delayed reaction when necessary. For example, some embodiments of the present disclosure provide low molecular weight and high performance materials for reducing cure times by minutes or hours in polymerization and days or weeks in molding. In one embodiment, the present invention can suppress chemical events due to activation of chemical components.
[0083] In some embodiments, the present disclosure provides materials and methods for polymerization, for example, in injection molding and reaction injection molding, that reduce or eliminate the need for high molecular weight materials that require high pressures with resulting high temperatures, and instead allow the molecular weight to be increased in process or in the mold, and as needed. Preferably, the matrix particles have a matrix material that is low molecular weight. The low molecular weight matrix particles of the present invention provide uniform mixing of the filler and provide higher performance adhesion without unwanted rheological issues. The present invention allows for less complex equipment and on-demand curing, which simplifies the preparation, storage, packaging, and handling of the materials.
[0084] The low molecular weight matrix particles provided by the present disclosure can be applied to various materials with various applications as adhesives. The present invention also provides localized heating or thermal activation. The matrix particles described herein provide the ability to activate polymerization as needed. The polymerization provided by the present invention can be activated through the substrate, fillers, other additives, etc. In other words, the opacity or lack of transparency of the bulk chemical mixture or pore-polymerization mixture does not significantly affect the progress of the reaction. The low molecular weight matrix particles described herein provide polymerization that does not depend on global heating or thermal activation.
[0085] The low molecular weight materials, i.e., matrix particles, of the present invention can be applied to a substrate in a pattern, thus providing a patterned adhesive. Low molecular weight matrix particle embodiments of the present invention can be applied in a pattern, thus providing a patterned adhesive, including both two-dimensional and three-dimensional selective activation.
[0086] In some embodiments, the matrix particles described herein provide on-demand polymerization of adhesives for producing fabricated products, including rigid or flexible laminates having two or more layers. In some embodiments, the matrix particles described herein provide polymerization of adhesives for pressure sensitive materials and their related products.
[0087] In one embodiment, the low molecular weight matrix particles of the present disclosure improve the cure of adhesives, coatings, etc., including substrates, passing energy through highly filled materials, opaque materials, etc.
[0088] Embodiments of the present invention provide materials and methods for improved non-metallic molding, polymer molding, and high speed mold manufacturing and delivery.
[0089] The method can also be carried out under ambient conditions. Thermal activation to initiate localized chemical events is achieved by application of electromagnetic radiation, such as radio frequency (RF) radiation or microwave radiation (MW).
[0090] For example, a matrix that melts, melts, expands, impacts, ruptures, and / or deforms due to heating of a susceptor element, such as a carbon nanotube, may liberate or activate a chemical moiety, such as a catalyst, which may then catalyze, for example, a polymerization reaction or a reaction that produces rapid energy.
[0091] Minimization of polymerization energy and precise control of polymerization
[0092] In one embodiment, the present invention relates to minimizing the energy required to activate chemical reactions and their effects, specifically the ability to avoid overall heating and minimize the penetration of limited energy, such as UV light, to activate one or more chemical events as needed in whatever order or series is desired.
[0093] Activation of chemistry and polymerization through opaque objects
[0094] In UV curing chemistries, uncontrolled rapid reactions can result in highly crosslinked systems. In some applications requiring toughness, uncontrolled UV curing reactions can cause unwanted vitrification and brittleness. An embodiment of the present invention provides a uniform distribution of catalyst / cocatalyst as an element of the matrix particles in the reaction mixture. Without being bound by theory, this uniform distribution in the reaction mixture allows for polymerization reactions to be initiated simultaneously at multiple sites, which aids in the production of a uniform polymer network. Without being bound by theory, reacting simultaneously at multiple sites results in controlled exotherm and improved efficiency.
[0095] Embodiments of the present invention provide for activation of a catalyst for polymerization at one or more depths in a matrix material. The catalyst may be located on the surface of the matrix material, at a depth below the surface, or embedded within the matrix material. For example, the catalyst may be located at a depth below the surface of up to about 0.01 μm, from about 0.01 μm to about 0.05 μm, from about 0.05 μm to about 0.1 μm, from about 0.1 μm to about 0.2 μm, from about 0.2 μm to about 0.3 μm, from about 0.3 μm to about 0.4 μm, from about 0.4 μm to about 0.5 μm, from about 0.5 μm to about 0.6 μm, from about 0.6 μm to about 0.7 μm, from about 0.7 μm to about 0.8 μm, from about 0.8 μm to about 0.9 μm, from about 0.9 μm to about 1 μm, from about 1 μm to about 5 μm, from about 5 μm to about 10 μm, or greater than about 10 μm, and any increment of depth therebetween.
[0096] In one embodiment, the present invention relates to solid state polymerization, where the molecular weight increases over time, where the polymer is already in a solid or highly viscous state, but by including particulates in the matrix, treatment with RF or MW, the polymerization yield or molecular weight can be increased, e.g., in situ.
[0097] Particle composition and structure
[0098] 5A and 5B, in some embodiments, the matrix particles of the present invention can be of a wide variety of configurations. The matrix material can be optionally deformable. In some embodiments, multiple matrices can be used in one embodiment. In some embodiments, one or more susceptor elements can be used. In some embodiments, one or more releasable and / or activatable components can be included in or on the matrix. In some embodiments, the one or more releasable and / or activatable components include one or more catalysts, cocatalysts, co-reactants, fuels, explosives, other components, and mixtures thereof. In some embodiments, the releasable and / or activatable components are released by one or more means including, for example, dissolution, expansion, decomposition (or impact, cracking), light, and / or one or more combinations thereof.
[0099] Variable Matrix Materials
[0100] As used herein, a "variable matrix" refers to a material that, when heated, can deform, dissolve, melt, rupture, expand, shrink, plasticize, and / or solvate to release its active ingredients (e.g., chemicals). The matrix particles can be of almost any geometric configuration, shape, or size. For example, as shown in FIG. 4, the matrix particles can be configured with shapes including one or more spheres, thin plates, ribbons, sheets, or coatings, rods or expanded fibers, porous structures including, e.g., foams, or one or more irregular or amorphous shapes.
[0101] In some embodiments, the matrix particles are continuous, as shown in Figures 5A and 5B. In some embodiments, the matrix material has an isotropic structure. In some embodiments, the matrix material is discontinuous. In some embodiments, the matrix material has an anisotropic structure or an orthotropic structure. In some embodiments, the matrix material is a mixture of one or more materials or structures. In some embodiments, the matrix material comprises a mixture of an isotropic structure and an anisotropic structure.
[0102] The matrix material may be composed of any suitable material, as understood in the art. In some embodiments, the matrix material may be a monomer, oligomer, or polymer. For example, the matrix may comprise methyl methacrylate. In some embodiments, the matrix material is composed of polymeric microparticles. For example, the polymeric microparticles may be made of one or more of polymethyl methacrylate (PMMA), styrene, and / or one or more of their polymers or copolymers. The microparticles may also be blends, alloys, and mixtures of polymers.
[0103] The polymeric microparticles can include polymeric microspheres and microcapsules, which can also be porous or have a partially open structure.
[0104] In some embodiments, the microparticles are spherical microparticles. The microparticles may have an effective diameter anywhere from about 0.1 μm to about 1000 μm. As used herein, "effective diameter" refers to the diameter of a comparable spherical microparticle of the same volume or weight. For example, the microparticles can have an effective diameter increase range of about 0.1 μm to about 0.5 μm, about 0.5 μm to about 1 μm, about 1 μm to about 5 μm, about 5 μm to about 10 μm, about 10 μm to about 50 μm, about 50 μm to about 100 μm, about 100 μm to about 200 μm, about 200 μm to about 300 μm, about 300 μm to about 400 μm, about 400 μm to about 500 μm, about 500 μm to about 600 μm, about 600 μm to about 700 μm, about 700 μm to about 800 μm, about 800 μm to about 900 μm, about 900 μm to about 1000 μm, and any range therebetween.
[0105] In some embodiments, the effective diameter of the microparticle is one of a number, measured in μm, or one of a number within a range defined by any two of the following numbers, inclusive: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, 500, 600, 700, 800, 900, and 1,000.
[0106] In one embodiment, microspheres as referred to herein are microparticles composed of homogeneous, solid polymer matrix materials, while microcapsules are core-shell microparticles, where the core can be solid, liquid, or hollow space. Microparticles can also be prepared as porous matrix materials composed of interconnected microspheres. Porous matrix materials can include pores formed on the surface, or pores on the exterior and / or interior. The pores can be independent or interconnected. The pores result in a matrix material with a very low mass density. The pores are suitable for trapping releasable and / or activatable components, such as susceptors, activators, catalysts, cocatalysts, co-reactants, oxidants, inhibitors, accelerators, and / or one or more other releasable components.
[0107] In some embodiments, the matrix material is composed of monodisperse polymer particles. In some embodiments, the matrix material is composed of polydisperse polymer particles. A polydispersion may include a narrow distribution of particle sizes (e.g., a monomodal distribution, a bimodal distribution, or a trimodal distribution). In some embodiments, a polydispersion includes an intermediate distribution of particle sizes. In some embodiments, a polydispersion includes a broad distribution of particle sizes. In some embodiments, the polydispersions have particle sizes ranging from about 1 nm to about 10 nm, from about 10 nm to about 50 nm, from about 50 nm to about 100 nm, from about 100 nm to about 200 nm, from about 200 nm to about 400 nm, from about 400 nm to about 600 nm, from about 600 nm to about 800 nm, from about 800 nm to about 1000 nm, from about 1 μm, from about 1 μm to about 1.5 μm, from about 1.5 μm to about 2 μm, from about 2 μm to about 2.5 μm, from about 2.5 μm to about 3 μm, from about 3 μm to about 3.5 μm, from about 3.5 μm to about 4 μm, from about 4 μm to about 4.5 μm, from about 4.5 μm to about 5 μm, and all increments therebetween. In some embodiments, the average particle size is up to about 0.1 μm. In some embodiments, the average particle size is about 0.1 μm to about 0.5 μm, about 0.5 μm to about 0.8 μm, about 0.8 μm to about 1 μm, about 1 μm to about 1.2 μm, about 1.2 μm to about 1.5 μm, about 1.5 μm to about 1.8 μm, about 1.8 μm to about 2 μm, about 2 μm to about 4 μm, about 4 μm to about 6 μm, about 6 μm to about 8 μm, about 8 μm to about 10 μm, about 10 μm The average particle size is in the range of about 20 μm, about 20 μm to about 40 μm, about 40 μm to about 60 μm, about 60 μm to about 80 μm, about 80 μm to about 100 μm, about 100 μm to about 200 μm, about 200 μm to about 400 μm, about 400 μm to about 600 μm, about 600 μm to about 800 μm, about 800 μm to about 1000 μm, and any and all values therebetween.
[0108] In some embodiments, the matrix material in the matrix particles has a molecular weight of up to 10 kDa. In some embodiments, the matrix material in the matrix particles has a molecular weight ranging from about 10 kDa to about 25 kDa, about 25 kDa to about 50 kDa, about 50 kDa to about 75 kDa, about 75 kDa to about 100 kDa, about 100 kDa to about 125 kDa, about 125 kDa to about 150 kDa, about 150 kDa to about 175 kDa, about 175 kDa to about 200 kDa, about 200 kDa to about 225 kDa, about 225 kDa to about 250 kDa, and all increments therebetween. Matrix materials having very high molecular weights (e.g., branched or crosslinked polymers such as rubber) are also within the scope of the present invention.
[0109] In some embodiments, the matrix material has a molecular weight, in kDa, given by any of the following values, or by a value within a range defined by any two of the following values, inclusive of the endpoints of such range, in kDa: 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10 000, 20000, 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000, 200000, 300000, 400000, 500000, 600000, 700000, 800000, 900000, and 1000000.
[0110] In some embodiments, the dispersion of polymer particles comprises particles having a low degree of crosslinking. In some embodiments, the dispersion of polymer particles comprises particles having a standard or medium degree of crosslinking. In some embodiments, the dispersion of polymer particles comprises particles having a high degree of crosslinking.
[0111] Susceptor
[0112] In some embodiments, the composition of matrix particles of the present disclosure includes one or more susceptors. In the present invention, a susceptor is a particle that can be heated or activated to generate heat. A susceptor is composed of a material that produces a higher heating rate (or rate) or a lower heat capacity compared to the surrounding or adjacent matrix material. The higher heating rate of the susceptor results in a change in the matrix upon application of an energy source, as defined above, without bulk heating the matrix material. A heated susceptor induces a change in the matrix material, whereby reaction-influencing elements or chemical components, such as catalysts or inhibitors, within the matrix can participate in one or more chemical reactions. An embodiment of a susceptor that can be heated includes one or more carbon-based or silicon carbide-based materials. The susceptor may include one or more ferrous or non-ferrous materials, including, for example, one or more transition metal oxides, ferrites, and / or one or more combinations thereof. Transition metals include Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn.
[0113] Iron susceptor embodiments include one or more of ferrite powder, superparamagnetic iron oxide (SPION) particles, and the like, including one or more combinations thereof.Susceptor embodiments include one or more of graphene, fullerene, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, filled or doped carbon nanotubes, carbon sheets, buckypaper, and the like, including one or more combinations thereof.
[0114] The susceptor embodiment is comprised of one or more materials that generate heat upon exposure to radio frequency (RF) radiation and / or microwave (MW) radiation, with microwave heating being used as an example to illustrate the method of the invention described below. Externally applied microwaves can generate matrix heating internally. Unlike conventional methods of bulk heating, the microwave-induced heating rate is not limited by the rate of heat transfer from an external heat source to the interior of the bulk reaction mixture. Thus, microwave heating is more efficient than conventional heating; that is, microwave heating heats the bulk reaction mixture with the matrix particles of the invention dispersed therein faster and more uniformly. Furthermore, conventional heating occurs via heat flow from an external heat source, whereas conventional heating propagates from the surface to the center of the bulk reaction mixture in one or more ways, including conduction and / or convection, throughflow, and mixing.
[0115] Thus, the surface of the bulk reaction mixture often remains at a higher temperature than the center of the bulk reaction mixture. For example, the outer surface of the reaction vessel in direct contact with the bulk reaction mixture heats the immediate area of the bulk reaction mixture with gradually lower temperatures toward the center. Even if an equilibrium temperature is established, the walls of the bulk reaction mixture adjacent to the reaction vessel are likely to be hotter to very hot, resulting in non-uniform yields and chemical properties in the bulk reaction mixture progressing toward the final product. For example, in a polymerization reaction, the bulk reaction mixture starting with monomers and oligomers may have a molecular weight distribution from the outside of the bulk reaction mixture toward the core depending on the temperature, or there may be higher decomposition closer to the reaction vessel, or there may be higher gelling / crosslinking at the walls of the reaction vessel.
[0116] This can result in uneven heating, overheating, and / or underheating causing non-uniformity of the reaction, which can then affect yield or cause problems with other reaction parameters. However, because microwave heating occurs uniformly both at the center and outside of the bulk reaction material, microwaves penetrate the matrix material and almost simultaneously thermally activate or excite the susceptors in the center of the bulk material, thereby generating heat within the bulk material, allowing the center of the matrix to remain at a uniformly higher temperature than the normal surface. That is, a localized heating source can be created with a very small size.
[0117] Thus, in some embodiments, the susceptor is disposed within the core of a matrix particle, such as a polymeric matrix material, and upon application of microwaves, the susceptor heats, thereby heating the core of the matrix particle, In some embodiments, the susceptor is disposed on the surface of the matrix particle, and upon application of microwaves, localized and rapid heating of the surface of the matrix material occurs.
[0118] Embodiments of the susceptor can be activated at one or more frequencies or ranges of frequencies. The frequencies may include one or more frequencies within the following ranges, including any of the following: up to about 100 MHz, about 100 MHz to about 200 MHz, about 200 MHz to about 400 MHz, about 400 MHz to about 600 MHz, about 600 MHz to about 800 MHz, about 800 MHz to about 1000 MHz, about 1000 MHz to about 1500 MHz, about 1500 MHz to about 2000 MHz, about 2000 MHz to about 2500 MHz, about 2500 MHz to about 5000 MHz, about 5000 MHz to about 7500 MHz, and all increments therebetween. A preferred frequency range is 900 MHz to 2500 MHz.
[0119] In some embodiments, the frequency is one of the following values, measured in MHz, or within a range defined by any two of the following endpoints, as follows: 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 35, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, and 7500.
[0120] Embodiments of the susceptor include one or more shapes. For example, the susceptor may be spherical, cylindrical, disk-shaped, tubular, or rectangular, one or more other regular prism shapes, one or more irregular shapes, and / or combinations thereof.
[0121] In some embodiments, the susceptor is functionalized. In some embodiments, the susceptor includes both functionalized and non-functionalized susceptors. In some embodiments, the functional groups include surface functional groups, where the functional groups are attached by one or more monomeric, polymeric surfactants. For example, in some embodiments, the susceptor may include one or more carboxyl groups, hydroxyl groups, methyl groups, etc. The susceptor may include one or more functional groups that increase or decrease hydrophilicity or hydrophobicity. The susceptor may include different functional groups such that regions of the susceptor are more hydrophilic or hydrophobic than other regions of the susceptor. For example, the susceptor may be functionalized such that the susceptor has a polar end and a non-polar end.
[0122] Releasable and / or Activatable Components
[0123] In some embodiments, the matrix material includes one or more releasable and / or activatable components, also known as releasable components or active components. The one or more releasable and / or activatable components may be encapsulated or incorporated into the matrix material, which may be a polymer or oligomer or monomer or a mixture of the three. For example, the one or more releasable components may be physically encapsulated or incorporated into one or more pores of the matrix material of the particulate. In some embodiments, the one or more releasable components may be chemically encapsulated within the polymeric matrix material. That is, the one or more releasable components may be chemically bound to one or more materials of the matrix within the matrix particle. The releasable components may include catalysts, cocatalysts, co-reactants, oxidizers, reaction inhibitor compounds, chelating agents, inhibitors, accelerators, activators (including surfactants, modifiers, fuels, explosives, and / or one or more combinations thereof). The releasable components can include any chemical, combination of chemicals, organic or inorganic, as is understood in the art. In some embodiments, the one or more releasable components can include one or more compounds capable of initiating polymerization, such as, for example, anionic, cationic, or free radical polymerization.
[0124] In some embodiments, the one or more releasable components include one or more components that initiate one or more reactions, including redox reactions such as in anaerobic adhesion. For example, the one or more releasable components can include one or more hydroperoxides and one or more transition metals. The one or more releasable components can be contained within different microcapsules, different pores within the matrix, trapped within the matrix material, bound to one or more components of the matrix material, or held apart and only come into contact when the matrix material is heated or activated.
[0125] In one embodiment, the one or more releasable components include one or more metal promoters or catalysts, such as ferrocene or other metallocenes. The one or more catalysts may be combined with peroxides and / or other compounds to activate or deactivate the polymerization. In some embodiments, the catalyst includes one or more of Cu-acetylacetone, Cu-2-ethylhexanoate, ferrocene, dimethylaminomethylferrocene, and / or one or more combinations thereof. In some embodiments, the one or more releasable components include one or more free radical stabilizers, such as hydroquinone or p-methoxyphenol.
[0126] In some embodiments, including compositions containing anionic cyanoacrylates and / or methylene malonates, the one or more releasable components may include one or more inorganic or organic bases (e.g., sodium propionate). In yet another embodiment, for cationic polymerization of epoxy resins, one or more components are released, such as diaryliodonium and triarylsulfonium, blocked super acids, cationic catalysts. In some embodiments, such as in condensation polymerization, the one or more releasable components may include one or more catalysts, such as antimony, germanium, titanium, and aluminum compounds.
[0127] Fuels, explosives, and the like are other examples where such materials may be used. Specifically, fuels or other explosive materials, alone or in combination with or without additional materials, can be utilized to initiate chemical reactions as described, and either alone or in combination with other reactive materials, release large amounts of energy in a variety of forms to facilitate events (e.g., from powering pistons in an engine, to explosive devices, incendiary events, to simple fast heating phenomena).
[0128] In one embodiment, the releasable components change the physical properties of the bulk reaction mixture, for example increasing or decreasing its viscosity, or providing color or other optical properties to the bulk reaction mixture, especially when chemical equilibrium is reached, e.g., to products.
[0129] particle structure
[0130] An embodiment of the present disclosure provides a matrix particle composition having a matrix material comprising one or more particles as described herein, one or more susceptors as described herein, and / or one or more releasable components as described herein. The matrix particle composition may be simply constructed as a matrix material comprising the susceptors and releasable components as described above, and may be present in any geometric configuration required by the application. For example, the matrix particles may be present in a spherical or approximately spherical structure, a ribbon or sheet-like structure, a rod-like or fiber-like structure, a porous structure including, for example, a foam, and / or one or more irregular structures. It should be noted that in some embodiments, the releasable components are not physically released, but rather may be chemically activated to perform their function.
[0131] In some embodiments, the composition of the matrix particles can have different phases including susceptors and / or activatable and / or releasable components. In some embodiments, the composition of the matrix particles can have a continuous phase including both susceptors and / or releasable components. In some embodiments, one or more susceptors and / or releasable components such as activators / catalysts can be included in a first layer of matrix material in the composition of the matrix particles and / or in one or more subsequent or alternating coating layers.
[0132] In some embodiments, the particle composition comprises one or more regions having hydrophilic chemistry, hydrophobic chemistry, and / or hydrophilic and / or hydrophobic chemistry. In some embodiments, one or more functionalized susceptors are arranged in or on the particle composition such that the functional groups of the susceptor and the particle chemistry are similarly arranged with a charge. For example, the hydrophilic regions of one or more susceptors are arranged to correspond with one or more regions of the matrix particle composition having one or more hydrophilic chemistry. Similarly, in some embodiments, the hydrophobic regions of one or more susceptors are arranged to correspond with one or more regions of the matrix particle composition having one or more hydrophobic chemistry. Thus, the arrangement of one or more susceptors in or on the matrix particle composition can be directed by the hydrophilic or hydrophobic regions of the matrix particle composition.
[0133] Embodiments of the matrix particle composition include configurations in which the susceptor is combined with a matrix material and one or more releasable components. Embodiments of the matrix particle composition include configurations in which the susceptor can be present on the surface of a first matrix material or in another matrix material that contacts the first matrix material. In some embodiments, the particle composition includes a first layer of matrix material and one or more additional adjacent layers of matrix material. For example, in some embodiments, the matrix particle composition can include a single matrix material or matrix material layer, two matrix material layers, three matrix material layers, etc. The matrix particle composition can include one or more homogeneous layers, one or more heterogeneous layers, and / or combinations thereof. For example, in some embodiments, more than one susceptor or susceptor type is included within a matrix particle composition. The additional susceptors can be disposed in the same matrix material layer, in adjacent matrix material layers, in alternating matrix material layers, etc.
[0134] In some embodiments, more than one releasable component, such as an activator or catalyst, is included in the same matrix material layer or in different matrix layers. The activators or catalysts may be located in the same matrix material layer, adjacent matrix material layers, alternating matrix material layers, etc. In some embodiments, more than one releasable component is included in the same matrix material layer or in different matrix layers. The releasable components may be located in the same matrix material layer, adjacent matrix material layers, alternating matrix material layers, etc.
[0135] In some embodiments, each matrix material layer comprises one combination of susceptor, activator / catalyst, and releasable component such as activator / catalyst. In some embodiments, each matrix material layer comprises more than one combination of susceptor and releasable component such as activator / catalyst. In some embodiments, the matrix particle composition comprises more than one matrix material layer, where each matrix material layer comprises the same combination of susceptor and releasable component such as activator / catalyst. In some embodiments, the particle composition comprises more than one matrix material layer, where each matrix material layer comprises a different combination of susceptor and releasable component such as activator / catalyst.
[0136] In some embodiments, the matrix particle composition comprises more than one matrix material layer, each layer is formulated to have a cure time within the same time period. In some embodiments, the matrix particle composition comprises more than one matrix material layer, each layer is formulated to have a cure time of different times, such as in a molded structure. In some embodiments, the layered matrix material is arranged to manage the stress and / or other physical properties of the material or particle composition applied to the matrix material. For example, in some embodiments, the particle composition is formulated with one or more activatable matrix components, activators, catalysts, releasable components, etc., in different amounts or concentrations.
[0137] The matrix particles may be supported or protected, in whole or in part, by a crushable or non-crushable support, including, for example, metal, ceramic, or glass, as the case may be, or may be supported or protected by a solid material coated or impregnated with the matrix particle composition, in a three-dimensional object such as a foam. To further illustrate, objects may be present that have roughened, spiked, or similar surface textures, for example, that underlie the structure but are prevented from being crushed by the matrix material surrounding the structure. Another example may include the matrix particle composition as coated beads, particles, granules, etc., and may include susceptors as metal glass beads or beads that melt or deform the matrix particle composition coated on their surface via heating.
[0138] In some embodiments, for example, multiple matrices are used if a particular application requires. The matrices can be formed in a variety of forms, including one or more coated layers, patterned films or layers, textured shapes, and the like.
[0139] In all applications, the susceptor is excited via external high frequency electromagnetic radiation (EMR) to partially or completely change, e.g., deform or dissolve or melt, the surrounding matrix or matrices, releasing (performing its function) catalysts, cocatalysts, inhibitors, co-reactants or accelerators, fuels, explosives, or other components. In some embodiments, the susceptor, such as CNTs, is excited or activated to heat or thermally activate the matrix. In some embodiments, heating or thermally activating the matrix transforms the matrix material.
[0140] Matrix particles offer an efficient way to deliver susceptors to formulations used in, for example, adhesives, coatings, composites, molding applications, and polymer systems. Using matrix particles as a carrier helps preserve rheological characteristics (e.g., CNTs, even at low loadings, cause viscosity spikes, resulting in processing issues). .
[0141] Various susceptors are also used depending on the particular application. For example, when curing opaque polymers, single and multi-walled carbon nanotube, sheet and fiber susceptors generally provide a very energy efficient susceptor material to heat and release a given catalyst. In other examples, CNTs along with boron nitride may be used for transparency when optical transparency is a driving factor.
[0142] The size of the susceptor elements can range in at least one dimension from the nanometer range to micrometers to millimeters, etc. For example, in some embodiments, the range in size of the susceptor elements can be any size range from about 1 nm to 10 nm, about 10 nm to about 100 nm, about 100 nm to about 1 μm, about 1 μm to about 10 μm, about 10 μm to about 100 μm, about 100 μm to about 1000 μm, and all increments therebetween.
[0143] In some embodiments, the size of the susceptor element is one of the following values measured in nm, or within a range defined by any two values, including the endpoints of the range in nm or any two additional values in nm: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 20000, 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000, 200000, 300000, 400000, 500000, 600000, 700000, 800000, 900000 and 1000000.
[0144] In some embodiments, the susceptor is uniformly dispersed in the matrix material. Dispersion of the susceptor allows for optimal use of the weight of the susceptor. In some embodiments, well-dispersed susceptor can result in strong van der Waals forces between the susceptor and the matrix material, without being bound by any theory as limiting the scope of the present invention. The interaction between the susceptor and the matrix can be via both covalent and non-covalent bonds.
[0145] The susceptor elements may include carbon nanotubes, carbon nanostructures, iron particles including superparamagnetic iron oxide nanoparticles (SPIONs), and the like.
[0146] Catalysts, cocatalysts, inhibitors, co-reactants, accelerators, fuels, explosives, other components, etc., and mixtures can be of virtually any composition, but preferably the final particles are present in concentrations appropriate for the required chemical function. Applications are highly unique and vary widely in their requirements.
[0147] In some embodiments, the concentration of the susceptor elements may generally range from 0.01% to 10%, depending on the application and the desires of the final decision maker. The energy requirement is derived from the deformation temperature and dynamics, heat transfer to the surrounding matrix, and duration of the event from milliseconds to tenths of a second. In some embodiments, the matrix includes one or more waxes. The waxes may include one or more natural waxes, such as carnauba wax. The waxes may include one or more synthetic waxes, such as polyethylene wax. The waxes may include a combination of both synthetic and natural waxes, which combination has a sharp melting point. In some embodiments, the waxes have a melting point and / or deformation temperature in the range between about 50°C and 300°C. For example, the wax matrix, in some embodiments, has a melting point of between about 50°C and about 75°C, between about 75°C and about 100°C, between about 100°C and about 125°C, between about 125°C and about 150°C, between about 150°C and about 175°C, between about 175°C and about 200°C, between about 200°C and about 225°C, between about 225°C and about 250°C, between about 250°C and about 275°C, between about 275°C and about 300°C, and all increments therebetween.
[0148] Wax as a matrix material
[0149] "Wax" means any wax, either naturally occurring or synthetic in origin. It may include blends or mixtures of one or more naturally occurring waxes and / or synthetic origin. Naturally occurring waxes include waxes of vegetable origin, animal waxes, and mineral waxes. Synthetic waxes are produced by physical or chemical methods. Being mixtures, naturally produced waxes are softer and melt at lower temperatures than the pure components.
[0150] Wax is C n H 2n+2where n varies from 13 to 80. Paraffin wax defined as n=13 is called tridecane, and when n=80 it is octacontane. C 13 The melting point of wax is -5.4°C. Similarly, the melting point of C60 wax is 100°C. Similarly, higher waxes (between C60 and C80) have melting points above 100°C. Depending on the temperature range to which the bulk reaction mixture needs to be heated, wax-based matrix particles can be tailored to have a center (or core) of a particular wax that changes, transforms, or melts within a particular temperature range.
[0151] Examples of vegetable waxes include mixtures of non-esterified hydrocarbons, which may be more than esters. Epicuticular waxes of plants are mixtures of substituted long chain aliphatic hydrocarbons including alkanes, alkyl esters, sterol esters, fatty acids, primary and secondary alcohols, diols, ketones, aldehydes, aliphatic aldehydes, primary and secondary alcohols, β-diketones, triacylglycerols, and many others. Specific examples of vegetable waxes include carnauba wax, candelilla wax, auricuri wax, jojoba wax, bayberry wax, Japan wax, sunflower wax, tall oil, tallow wax, rice wax, and tallow.
[0152] Animal waxes include beeswax and waxes secreted by other insects. The main component of beeswax used in beehives is myricyl palmitate, an ester of triacontanol and palmitic acid. Spermaceti is found in large amounts in the blubber of sperm whales. One of the main components is cetyl palmitate, an ester of other fatty acids and fatty alcohols. Lanolin is a wax obtained from wool and is composed of esters of sterols. Other examples of animal waxes include lanocerin, shellac, and ozokerite.
[0153] Examples of mineral waxes include montan wax, paraffin wax, microcrystalline wax, and intermediate wax. While many natural waxes contain esters, paraffin wax is a hydrocarbon, usually a mixture of alkanes in the homologous series of chain lengths. Paraffin wax is a mixture of saturated n- and iso-alkanes, naphthenes, and alkyl- and naphthenic-substituted aromatics. The degree of branching has a significant effect on the properties. Montan wax is a fossil wax extracted from coal and lignite. It is very hard, reflecting a high concentration of saturated fatty acids / esters and alcohols. Montan wax contains chemical components formed of long-chain alkyl acids and alkyl esters with a chain length of about 24-30 carbons. In addition, natural montan contains resin acids, polyterpenes, and some alcohols, ketones, and other hydrocarbons, and is not a "pure" wax. As a saponifiable wax, montan has a saponification value of about 92 and its melting point is about 80°C. In addition to montan wax, other waxes of natural origin are also known for use in various industries, including petroleum waxes obtained from crude oil after processing, including macrocrystalline wax, microcrystalline wax, petroleum wax and paraffin wax. Paraffin wax is also a natural wax obtained from petroleum and is mainly composed of linear alkanes with an average chain length of 20 to 30 carbon atoms.
[0154] Synthetic waxes include waxes based on polypropylene, polyethylene, and polytetrafluoroethylene. Other synthetic waxes are based on fatty acid amines, Fischer-Tropsch, and polyamides. Polyethylene and related derivatives. Some waxes are obtained by decomposing polyethylene at 400°C. The products have the formula (CH2) n H2, where n ranges between about 50 and 100.
[0155] Synthetic waxes, including low molecular weight synthetic polyethylene waxes (i.e., molecular weights less than about 10,000) and polyethylenes having wax-like properties are known. Such waxes are formed by the direct polymerization of ethylene under appropriate conditions to control the molecular weight. Polyethylenes having molecular weights in the range of about 2,000 to 4,000 are waxes, and those in the range of about 4,000 to 12,000 are wax resins.
[0156] Fischer-Tropsch waxes are polymethylene waxes produced by certain polymerization syntheses, specifically Fischer-Tropsch synthesis (polymerization of carbon monoxide at high pressure, high temperature and special catalysts to produce hydrocarbons, followed by distillation to separate the products into liquid fuels and waxes). Such waxes (hydrocarbon waxes of the microcrystalline, polyethylene and polymethylene type) can be modified chemically, for example by air oxidation (giving an acid number of 30 or less, and a saponification number not less than 25), or with maleic anhydride or carboxylic acid. Such modified waxes are more easily emulsified in water and can also be saponified or esterified. Other known synthetic waxes are polymerized alpha-olefins. These are waxes formed with higher alpha-olefins of 20 or more carbon atoms and have wax-like properties. This material is highly branched, has a broad molecular weight distribution, has a melting point range of about 54°C to 75°C, and has a molecular weight of about 2600 to 2800. Thus, waxes vary depending on the nature of the base material and the polymerization or synthesis method, and on the resulting chemical structure, including the use and type of any chemical modifications.
[0157] The matrix particles may be produced by polymerization, or by physical material disruption, emulsion polymerization, dispersion polymerization and / or suspension polymerization, core-shell polymerization, solvent dispersion, cavitation of fluids and / or solids in a fluid, amalgamation of susceptors and catalysts, amalgamation followed by pulverization, grinding, and the like.
[0158] As shown in Figure 1, a solid matrix particle is shown comprising carbon nanotubes as susceptor elements and a catalyst for promoting a chemical reaction. High frequency (radio frequency) radiation is applied to the matrix particle, heating the carbon nanotube particles. These particles are embedded in the vicinity of the catalyst particles. The matrix material fully or partially melts or deforms, and as a result of the high frequency, the catalyst is released to subsequently catalyze a reaction of a material in which the matrix particles are embedded.
[0159] In this embodiment, the RF or MW energy only heats and melts the matrix particles. The heating rate of the matrix particles is orders of magnitude higher than the adjacent materials. The selective heating of the matrix particles results in the deformation of the matrix particles without causing bulk heating. Furthermore, the uniformly distributed matrix particles and the size of the particles cause little heating of the adjacent blend. As a result, the RF and MW energy activates the release of the matrix particle contents and induces uniform and rapid polymerization. In one embodiment, a catalyst is required, typically in the ppm range of 2% or less. In one embodiment, the percentage of catalyst is any number selected from the numbers provided below, or within a range defined by any two of the following numbers as endpoints: 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, and 2.0.
[0160] Figure 2 shows reaction injection molding as it is currently practiced and reaction injection molding according to the present invention. As a result of the present invention, no complex mixing is required. Instead of heat curing, RF curing is performed. By eliminating or reducing the use of steel molds, the reaction can be accomplished under lower pressures without the application of total heat, and the reaction is faster. It also significantly reduces the cure time.
[0161] As currently practiced, for film laminating adhesives, multiple film lines are used for multiple layers, as shown in Figure 3. With the present invention, one line can be used for multiple layers. The advantages are high speed, no heating required, the ability to cure opaque materials, and no depth limitations. In addition to tight control over when cure occurs during production, control over the location of cure is also achieved.
[0162] In one embodiment, the RF or MW is a directional source, with the radiation being focused on a particular object or region of interest.
[0163] In an embodiment, the matrix may have a coating. In some embodiments, the coating is continuous. In some embodiments, the coating is discontinuous. In some embodiments, the coating is patterned. In some embodiments, the coating is disposed in one or more layers. In some embodiments, the coating is anisotropic.
[0164] In some embodiments, the coating is attached to the matrix by one or more means including, for example, entanglement, van der Waals interactions, via one or more chemically binding compounds, etc. In some embodiments, the coating comprises one or more waxes, one or more hydrophilic compounds and / or one or more compounds having a non-polar component with a non-polar tail, including hydrophilic functional groups, one or more oils, fatty acids, etc.
[0165] The coating may have a thickness of any of up to 10 nm, from about 10 nm to about 15 nm, from about 50 nm to about 100 nm, from about 100 nm to about 500 nm, from about 500 nm to about 1 μm, from about 1 μm to about 2 μm, from about 2 μm to about 5 μm, from about 5 μm to about 10 μm, from about 10 μm to about 50 μm, from about 50 μm to about 100 μm, from about 100 μm to about 500 μm, from about 500 μm to about 1 mm, from about 1 mm to about 2 mm, from about 2 mm to about 5 mm, from about 5 mm to about 10 mm, from about 10 mm to about 50 mm, from about 50 mm to about 100 mm, from about 100 mm to about 500 mm, and all increments therebetween.
[0166] Embodiments of the matrix may include one or more additional elements to provide controlled, on-demand release, such as coated or uncoated matrix and / or coatings and / or discontinuous coatings comprising the matrix on any surface that is amenable to activation of the matrix, such as round fibers, woven fibers, polymeric fibers, hollow fibers, reinforcing fibers such as those utilized in composites, sheets, flexible or non-flexible materials, foams and other porous structures, nonwovens, woven fabrics, polymeric scrims, reinforcing scrims, etc.
[0167] In some embodiments, the matrix includes one or more fillers. Filler embodiments include particles such as fibers. The fibers may have one or more lengths. The fibers may include ground fibers. Filler embodiments include one or more clays, aggregates, plasticizers, plastic particles, nanoparticles of various shapes, and the like.
[0168] Method and apparatus for activating particles
[0169] The particle activation methods and apparatus comprise a complete "system" that includes various types of susceptors, activators, matrix elements, RF and / or MW energy sources, material handling, software, and controls.
[0170] Speed, time, unit throughput, formation factor, topology, and unit volume are among the dependent characteristics that are analyzed for each application and adjusted by the system to produce the desired end product or outcome for a given set of materials.
[0171] The susceptor is excited via external high frequency EMR to partially or fully deform the surrounding matrix or matrices to release (or activate) the catalyst, co-catalyst, co-reactant, or accelerator. In areas such as the remote Joule heating properties of CNTs, the heated CNTs are used to deform the surrounding matrix, although not being bound by theory of the physics of how CNTs heat the surrounding material.
[0172] In the most common form, microwave electromagnetic radiation having a wavelength range of about 1 m to about 1 mm, i.e., frequencies between 300 MHz (1 m) and 300 GHz (1 mm), is used to excite the susceptor, deform the surrounding matrix, and release the catalyst or active material. In practice, a variety of electromagnetic wavelengths and frequencies can be used, with frequencies of 915 MHz and 2450 Mhz being the most common currently for consumer and industrial applications. However, one or more suitable frequencies may include any of the following frequencies up to about 100 MHz, from about 100 MHz to about 200 MHz, from about 200 MHz to about 400 MHz, from about 400 MHz to about 600 MHz, from about 600 MHz to about 800 MHz, from about 800 MHz to about 1 GHz, from about 1 GHz to about 1.5 GHz, from about 1.5 GHz to about 2 GHz, from about 2 GHz to about 2.5 GHz, from about 2.5 GHz to about 5 GHz, from about 5 GHz to about 7.5 GHz, and all increments therebetween.
[0173] [Table 1]
[0174] In one embodiment of the invention, the method of applying electromagnetic radiation, i.e., irradiating the bulk reaction mixture, is carried out for a period of 10 seconds to 60 seconds. In another embodiment, the irradiation time, in seconds, is any one number selected from the following, or a number within a range defined by any two of the following numbers, inclusive of the range endpoints: 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, 3100, 3200, 3300, 3400, 3500 and 3600.
[0175] In one embodiment of the invention, EMR is used as a beam to irradiate the bulk reaction mixture, which is exposed to RF or MW radiation.
[0176] Purpose
[0177] Exemplary applications include, but are not limited to, the following:
[0178] Adhesive bonding
[0179] Catalysts, co-catalysts, and / or accelerators, etc., can be released on demand, whereby the constraints of overall heating, mixing of multiple components, long polymerization times, and / or depth limitations as with light and / or surface primer activation systems can be eliminated by dispersing the components as desired within the polymerizable composition and activating as desired at the desired time within the bonding or adhesion process and / or part preparation method, and advantages include very precise positioning without reactions that change viscous dynamics.
[0180] coating
[0181] Catalysts, co-catalysts, and / or accelerators can be released on demand, whereby overall heating, mixing of multiple components, long polymerization times, and / or depth limitations as with light and / or surface primer activation systems can be eliminated by dispersing the components as desired within the polymerizable composition and activating them on demand at the desired time within the coating or coating method and / or part preparation method. Benefits also include flow control prior to and without reactions that change viscosity dynamics. Limitations of UV curable systems, such as incomplete cure in shadow areas or parts with complex shapes, can be overcome. There are no limitations when curing 3D and recessed parts with large appendages. Cure speeds can be matched in upstream and downstream processes, eliminating bottlenecks in manufacturing throughputs.
[0182] Molded and Composite
[0183] Catalysts, cocatalysts, and / or accelerators, etc., are released as needed, whereby the constraints of total heating, mixing of multiple components, long polymerization times, and / or depth limitations, such as with light and / or surface primer activation systems, can be eliminated by dispersing the components as desired within the polymerizable composition and activating as needed at the desired time within the molding or forming method and / or method of preparing the part. Parts can be filled with many materials. Parts can be as large as or larger than 14 feet by 14 feet in cross section. In the context of this description, all publications, patent applications, patents, and other references mentioned herein are expressly incorporated by reference herein for all purposes, unless otherwise noted, as if fully set forth in their entirety.
[0184] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this disclosure belongs. In case of conflict, the present specification, including definitions, will control.
[0185] Unless expressly noted, trademarks are shown in capital letters.
[0186] Unless otherwise specified, all percentages, parts, ratios, etc. are by weight.
[0187] Unless otherwise noted, pressures expressed in psi are gauge pressures and pressures expressed in kPa are absolute pressures, however pressure differences are expressed in absolute pressures (e.g., pressure 1 is 25 psi higher than pressure 2).
[0188] When an amount, concentration, or other numerical value or parameter is given as a range, or a list of upper and lower limits, this is to be understood as specifically disclosing all ranges formed from any upper and lower range values, regardless of whether the ranges are disclosed individually. When a range of numerical values is described herein, unless otherwise indicated, the range is intended to include the endpoints of the range, and all integers and fractions within the range. It is not intended that the scope of the disclosure be limited to the specific values recited when defining a range.
[0189] When the term "about" is used, it is intended that a certain effect or result can be obtained within a certain tolerance, and one of ordinary skill in the art knows how to obtain that tolerance. When the term "about" is used to describe a numerical value or an endpoint of a range, it should be understood that the disclosure includes the specific value or endpoint referenced.
[0190] As used herein, the words "comprises," "comprising," "includes," "including," "has," "having," or any other variation of these terms are intended to cover a non-exclusive inclusion. For example, a process, method, article, or apparatus comprising a list of elements is not necessarily limited to only those elements but can include other elements not expressly listed or inherent to such process, method, article, or apparatus.
[0191] The transitional phrase "consisting of" excludes any element, step, or ingredient not specified in the claim and excludes the inclusion of any material in a claim other than those recited, except for impurities normally incident to such materials. When the phrase "consists of" appears in a clause in the body of a claim rather than immediately following the preamble, it limits only the elements recited in that clause and does not exclude other elements from the claim as a whole.
[0192] The transitional phrase "consisting essentially of" limits the scope of the claim to the materials or steps specified and which do not materially affect the basic and novel features of the claimed invention. A claim containing "consisting essentially of" represents a middle ground between a closed claim written in the "consisting of" format and a completely open claim written in the "comprising" format. Any additives defined herein are at the appropriate levels for such additives, and trace amounts of impurities are not excluded from the composition by the term "consisting essentially of."
[0193] Furthermore, unless otherwise noted, "or" and "and / or" refer to an inclusive and not an exclusive term. For example, condition A or B, or A and / or B, can satisfy any one of the following: A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (exist).
[0194] The use of "a" or "an" to describe various elements and components herein is merely for convenience and to give a general sense of the disclosure. Such use should be interpreted to include one or at least one, and the singular also includes the plural unless it is clear that it is meant otherwise.
[0195] Experimental Examples
[0196] Example 1 - Polymerization of methylene malonate by anionic polymerization
[0197] composition
[0198] This example relates to a curable composition comprising matrix particles, the composition comprising: (a) Methylene malonate monomer (b) a stabilizer solution, and (c) Activator Consisting of (i) the activator comprises a cation at a level of 0.1 to 500 ppm; and (ii) The activator is encapsulated in heat deformable and / or heat fusible matrix particles that also contain RF susceptors (eg, carbon nanostructures).
[0199] combination
[0200] Prepare the following formulations by weight %, adding other modifications as desired: 1. Difunctional or higher functional methylene malonate monomers, oligomers, or resins: 20% to 70.0%; 2. Diethyl, dipropyl, dibenzyl, diisobornyl or similar methylene malonate monomers: 20% to 70%; and 3.Acid stabilizer solution: 0.1%~0.7%.
[0201] To the above formulation is added 50-5000 nanometer matrix particles comprising 90% paraffin wax, or olefinic polymer or oligomer wax, etc., 8% carbon nanotubes, and 2% activator, such that the particles represent 5 ppm of activator cations in the final overall composition.
[0202] Matrix Consideration
[0203] Overall, the activator range is 0.5 ppm to 500 ppm, which is achieved by varying the concentration of matrix particles anywhere from 0.5% to 10%, and the power level which determines the appropriate frequency, power level and therefore the time required to activate and ultimately polymerize the particles.
[0204] MF-Transparent filler
[0205] The formulation as made above can then be adjusted by using chemically neutral, optionally dry RF transparent fillers such as calcium carbonate, glass or glass powders, inorganic such as polymer powders, wood or other organic powders, silica, silicates, and ceramics. If moisture is an issue, a combination of transition metal promoters (especially copper hexanoate and iron, specifically ferrocene) can be used.
[0206] Curing, Substrates and Containers
[0207] Different formulations will change the cure rate and therefore the exotherm of polymerization. Therefore, one should start by placing a small amount of the formulation so that a thin film is placed between two glass slides, thus minimizing material and creating anaerobic conditions to allow observation. In the next step, spacers can be added to create a thicker bond. In the next step, one can move to narrower test tubes and / or syringe bodies. Then, one can scale up to larger test tubes and / or syringe bodies. Then, one can scale up to small beakers. Larger volume material assemblies and / or containers can be placed in oil and / or water to control the heat transfer of the exotherm and avoid dangerous situations.
[0208] Essentially, it is desirable for an RF transparent material to be in the containment vessel or part of the containment vessel so as to adequately transmit the necessary RF energy.
[0209] Example 2 - Free Radical Polymerization via Anaerobic Polymerization
[0210] composition
[0211] This example relates to a curable composition: (a) Acrylate and / or methacrylate monomers (b) a hydroperoxide or perester initiator, and (c) Activator Consisting of (i) the activator comprises a source of copper ions at a level of 0.1 to 100 ppm copper; (ii) The active agent is encapsulated within heat deformable and / or heat fusible matrix particles that also contain an RF susceptor.
[0212] combination
[0213] Prepare the following formulations by weight %, adding other modifications as desired: 1. Triethylene glycol dimethacrylate, urethane diacrylate, or epoxy diacrylate: 20% to 70.0% 2. Lauryl, ethyl, methyl, ethylhexyl, cyclohexyl, isobornyl methacrylate: 20%~70% 3. Cumene hydroperoxide: 0.5% to 3.0% 4. Stabilizer solution*: 0.3%~0.7% 5. Saccharin: 0.1% to 0.5%.
[0214] To these formulations are added: 50-5000 nanometer matrix particles comprising 90% by weight of one or more of paraffin wax, olefinic polymer, oligomeric wax or similar matrix; 8% carbon nanotubes; and 2% copper ethylhexanoate activator. These ingredients are added such that the particles represent 0.6 ppm copper in the final composition.
[0215] Instead of 2% copper, 0.06% can also be added to a formulation of 50% particle dispersion with 2% ferrocene in the particles.
[0216] Matrix Review
[0217] The concentration range of copper hexanoate is 0.6 ppm to 60 ppm, which is achieved by varying the concentration of the matrix particles from 0.5% to 10% of the compound in the matrix particles, and the appropriate RF wavelength, power level, and therefore the power level, which determines the time required to activate and polymerize the particles.
[0218] RF-Transparent Filler
[0219] Formulations made as above were prepared using chemically neutral, possibly dry RF transparent fillers, such as calcium carbonate, many inorganics such as glass or glass powder, polymer powders, wood or other organic powders, silica, silicates, ceramics, etc. When moisture is an issue, a combination of transition metal accelerators (especially copper hexanoate and iron, specifically ferrocene) is used.
[0220] Curing, Substrates and Containers
[0221] Different formulations change the cure rate and therefore the exotherm of polymerization. Therefore, first a small amount of the formulation is placed between two glass slides as a thin film, thus minimizing material, creating anaerobic conditions and allowing observation. Then a spacer is added to create a thick bond. Then move to a narrow test tube and / or syringe body. Then scale up to a larger test tube and / or syringe body. Then scale up to a small beaker. Larger volumes of material and / or containers can be placed in oil and / or water to control the heat transfer of the exotherm and avoid dangerous situations. Essentially, it is desirable for an RF transparent material to be the containment vessel or part of the containment vessel so that the necessary RF energy can be properly conducted.
[0222] Example 3 - Method using commercially available microparticles as the core
[0223] This study shows that available microparticles can be used as the core of matrix particles to carry activators and initiate curing in one-part adhesive formulations. The main objective of this study is to show that commercially available PMMA can be used in micro / nano scale particles as a carrier for acrylic activators by attaching copper activators to the surface of the commercial particle core.
[0224] [Table 2]
[0225] **MX-500ML, MP-1441, and MX-180TA were obtained from Soken (Japan), and XX6666Z was obtained from Sekisuikasei (Japan).
[0226] The following formulations were prepared to evaluate the conditions for preparing matrix particles using various commercially available PMMA particles as the core of the matrix particles.
[0227] Formulation 1 - Commercially available PMMA (MX-500ML) (2 g) was filter washed first with 10% (100 mL) sodium hydroxide solution, then with 10% (10 mL) cupric chloride solution, rinsed with deionized water and dried.
[0228] Formulation 2 - Commercially available PMMA (MX-500ML) (2 g) was filter washed first with 10% (100 mL) sodium hydroxide solution, then with 10% (10 mL) cupric chloride solution, rinsed with deionized water and dried.
[0229] Formulation 3 - Commercially available PMMA (MP-1441) (2 g) was filter washed first with 10% (100 mL) sodium hydroxide solution, then with 10% (10 mL) cupric chloride solution, rinsed with deionized water and dried.
[0230] Formulation 4 - Commercially available PMMA (XX6666Z) (2 g) was filter washed first with 10% (100 mL) sodium hydroxide solution, then with 10% (10 mL) cupric chloride solution, rinsed with deionized water and dried.
[0231] Formulation 5 - Commercially available PMMA (MP-1441) (5 g) was sonicated with copper(II) 2-ethylhexanoate (1 g) in isopropanol and filter washed with additional isopropanol.
[0232] Formulation 6 - Commercially available PMMA (MX-180TA) (2 g) was sonicated with a solution of cupric chloride (0.125 g) in isopropanol and filter washed with additional isopropanol.
[0233] Formulation 7 - Commercially available PMMA (MX-180TA) (4 g) was sonicated with copper(II) 2-ethylhexanoate (0.21 g) in isopropanol and filter washed with additional isopropanol.
[0234] Formulation 8 - Commercially available PMMA (MX-180TA) (4 g) was sonicated with a solution of cupric chloride (0.2 g) in isopropanol and vacuum filtered.
[0235] Example 4 - Preparation of particle cores via emulsion polymerization
[0236] The main goal of this study is to prepare nanoparticulate cores via emulsion polymerization, specifically, emulsion polymerization of methacrylates. An exemplary reaction schematic is shown in Figure 18. Formulations were prepared using oil-in-water emulsions of methacrylates in water for emulsion polymerization into nanoparticles.
[0237] Experiment 1 Methyl methacrylate (3 mL) was added to deionized water (16 mL) at 70° C. and emulsified under inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (10-15 mg) and stirred for 30 min.
[0238] Experiment 2 Methyl methacrylate (3 mL) was added to deionized water (16 mL) at 70° C. and emulsified under inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (10-15 mg) and stirred at 450 rpm for 40 min.
[0239] Experiment 3 Methyl methacrylate (3 mL) was added dropwise to deionized water (16 mL) over 30-40 min at 70°C and emulsified under inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (10-15 mg) and stirred for 40 min.
[0240] Experiment 4 : Copper(II) 2-ethylhexanoate was dissolved in methyl methacrylate (3 mL) and poured into deionized water (16 mL) under inert gas at 70°C. ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (10-15 mg) was added and stirred at 350 rpm for 40 minutes.
[0241] Example 5: Method for preparing hollow particle cores
[0242] This study demonstrates a method for preparing hollow particle-core structures. Representative SEM images of hollow particles are shown in Figure 7, and representative SEM images of hollow core particles combined with SPIONs and copper are shown in Figure 8.
[0243] Experiment 1
[0244] A solution of 5-6% w / w PMMA (120,000 g / mol) dissolved in dichloromethane (DCM) was added dropwise to an aqueous medium of polyvinyl alcohol (0.5%-0.6% w / v) and stirred at 500-550 rpm for 10-15 min. The solution was left overnight or for 12-18 h until the DCM had evaporated. The hollow particles were filter washed three times with isopropanol and again left to dry.
[0245] Experiment 2
[0246] A solution of 5-6% w / w PMMA (15,000 g / mol) dissolved in dichloromethane was added dropwise to an aqueous medium of polyvinyl alcohol (0.5%-0.6% w / v) and stirred at 500-550 rpm for 10-15 min. The solution was left overnight or for 12-18 h until the DCM had evaporated. The hollow particles were filter washed three times with isopropanol and again left to dry.
[0247] Experiment 3
[0248] A first solution was prepared by dissolving copper(II) 2-ethylhexanoate (12.5 mg) in dichloromethane. A second solution of 5-6% w / w PMMA (15,000 g / mol) dissolved in the first solution was added dropwise to an aqueous medium of polyvinyl alcohol (0.5%-0.6% w / v) and stirred at 500-550 rpm for 10-15 min. The solution was left overnight or for 12-18 h until the DCM had evaporated. The hollow particles were filter washed three times with isopropanol and again left to dry.
[0249] Experiment 4
[0250] A dispersion of SPIONs (12.5 mg) in dichloromethane was prepared. 5-6% w / w PMMA (15,000 g / mol) dissolved in the SPION / dichloromethane dispersion was added dropwise to an aqueous medium of polyvinyl alcohol (0.5%-0.6% w / v) and stirred at 500-550 rpm for 10-15 min. The solution was left overnight or for 12-18 h until the DCM had evaporated. The hollow particles were filter washed three times with isopropanol and left again to dry.
[0251] Experiment 5
[0252] A dispersion of oleic acid modified SPIONs (12.5 mg) in dichloromethane was prepared. 5-6% w / w PMMA (15,000 g / mol) dissolved in the SPION / dichloromethane dispersion was added dropwise to an aqueous medium of polyvinyl alcohol (0.5%-0.6% w / v) and stirred at 500-550 rpm for 10-15 min. The solution was left overnight or for 12-18 h until the DCM had evaporated. The hollow particles were filter washed three times with isopropanol and left again to dry.
[0253] Test 6
[0254] A dispersion of oleic acid modified SPIONs (12.5 mg) and copper(II) 2-ethylhexanoate (12.5 mg) in dichloromethane was prepared. 5-6% w / w PMMA (15,000 g / mol) dissolved in the SPION / dichloromethane dispersion was added dropwise to an aqueous medium of polyvinyl alcohol (0.5%-0.6% w / v) and stirred at 500-550 rpm for 10-15 min. The solution was left overnight or for 12-18 h until the DCM had evaporated. The hollow particles were filter washed three times with isopropanol and again left to dry.
[0255] Example 6 - Method for preparing a core by fusing a susceptor and a catalyst
[0256] This work demonstrates remote activation of susceptors by microwaves within matrix particles. The matrices used in this work were prepared by combining susceptors and other components of the matrix particles as an amalgamation. The matrix particles were exposed to microwaves to release the activators and perform their functions. For example, in some cases, microwaves heated the susceptors, carbon nanotubes, which released copper catalyst from the matrix particles and catalyzed the polymerization reaction.
[0257] Experiment 1
[0258] Solution A was prepared by dissolving 5g PMMA in xylene at 80°C for 20-30 minutes. Solution B was prepared by melting 5g carnauba wax in xylene with a heat gun. A and B were mixed very slowly with continuous heating. Copper(II) 2-ethylhexanoate (0.5%) was added to the solution of A and B. The solution was heated to 110°C with continuous stirring until most of the xylene had evaporated. Before all had evaporated, 10% carbon nanostructures were added and mixed with high shear. Once enough xylene had evaporated and the solution had turned to a paste, the solution was crumbled in ethanol. The solid was ground with water in a blender and dried overnight to obtain a powder. The powder was sieved through a micron mesh to obtain the core particles.
[0259] Experiment 2
[0260] A dispersion of 0.1 g of carbon nanostructure pellets was made in 30 mL of dichloromethane, followed by a solution of 3 g of hexadecyl trimethyl ammonium bromide (CTAB) dissolved in 10 mL of isopropanol and 20 mL of dichloromethane with mixing at 700 rpm. Copper(II) 2-ethylhexanoate was added to the solution along with a solid plasticizer (Benzoflex™ 352) with continuous stirring. The sample was left to stir until dry.
[0261] Experiment 3 A mixture of 0.1 g carbon nanotubes and 0.2 g CTAB was made in 30 mL dichloromethane and sonicated for 15 minutes at 30% power. An additional 50 mL dichloromethane was added and the sample was sonicated for an additional 15 minutes at 30% power. 9.9 g Benzoflex™ 352 (a solid plasticizer) and 1 g copper(II) 2-ethylhexanoate were added and mixed by hand. A stir bar was placed into the sample and stirred on a hot plate at 35° C. and 700 rpm to keep the particles suspended while the dichloromethane evaporated.
[0262] Experiment 4
[0263] 0.11 g of the mixture of particles from experiment 1 was dispersed in 10 mL of dimethyl malonate by sonication for 10 min. A drop of these particles was placed on a microscope slide and tested by heating in a microwave oven for 60 s at 800 W / 4 V.
[0264] Example 7 - Method for coating microparticles with a susceptor
[0265] This work describes a method to coat microparticles (eg, commercially available PMMA microparticles) with susceptors such as carbon nanotubes (CNTs) or carbon nano-substances (CNS).
[0266] Experiment 1
[0267] In this experiment, 250 mg of PMMA (Soken MX-500ML) was added to 50 mL of water. It was then sonicated at 20% amplitude for 30 minutes using a microprobe sonicator. In another flask, 300 mg of CNTs was added to 120 ml of water. This was then sonicated at 10% amplitude for 15 minutes using a probe sonicator. The PMMA and water dispersion was taken in a beaker and stirred continuously at room temperature to avoid the PMMA particles settling. Next, 10 mL of CNTs dispersed in water was taken in a syringe and added dropwise at 0.5 ml / min to the PMMA dispersion using a syringe pump. The sample was left overnight to allow the coated PMMA particles to settle. The particles were then separated using a centrifuge.
[0268] Experiment 2
[0269] In this experiment, 250 mg of PMMA (Soken MX-500ML) was added to 50 mL of water. It was then sonicated at 20% amplitude for 30 minutes using a microprobe sonicator. In another flask, 300 mg of CNS was added to 120 mL of water. This was then sonicated at 10% amplitude for 15 minutes using a probe sonicator. The PMMA and water dispersion was taken in a beaker and stirred continuously at room temperature to avoid settling of the PMMA particles. Next, 10 mL of CNTs dispersed in water was taken in a syringe and added dropwise at 0.5 ml / min to the PMMA dispersion using a syringe pump. The sample was left overnight to allow the coated PMMA particles to settle. The particles were then separated using a centrifuge.
[0270] Experiment 3
[0271] In this experiment, 1 ml of PMMA prepared using the emulsion polymerization method described above was added to 9 ml of water. In a separate flask, 300 mg of CNTs were added to 120 ml of water. This was sonicated at 10% amplitude using a microprobe ultrasonicator for 15 minutes. The dispersion of CNTs and water was taken in a beaker and stirred continuously at room temperature. Next, 10 ml of PMMA dispersed in water was taken in a syringe and added dropwise at 0.5 ml / min to the CNT dispersion using a syringe pump. The sample was left overnight to allow the coated PMMA particles to settle. The particles were then separated using a centrifuge.
[0272] Example 8 - Method for preparation of microparticles via emulsion copolymerization
[0273] This work provides a method for functionalizing PMMA by copolymerizing it with various copolymers, including poly(ethylene glycol) methacrylate (PEGMA), poly(ethylene glycol) dimethacrylate (PEGDMA), stearyl methacrylate, and methacrylic acid.
[0274] Experiment 1
[0275] Methyl methacrylate (12 mL) was added dropwise to deionized water (64 mL) at 70 °C and emulsified in the presence of inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 30-40 min. An additional 20 mg of AIBN was added along with 1.2 mL of poly(ethylene glycol) methacrylate (PEGMA) and stirred for 40 min.
[0276] [ka] PEGMA
[0277] Experiment 2
[0278] Methyl methacrylate (12 mL) was added dropwise to deionized water (64 mL) at 70 °C and emulsified in the presence of inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 10 min. An additional 20 mg of AIBN was added along with 1.2 mL of poly(ethylene glycol) methacrylate (PEGMA) and stirred for 40 min.
[0279] Experiment 3
[0280] Methyl methacrylate (12 mL) was added dropwise to deionized water (64 mL) at 70 °C and emulsified in the presence of inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 10 min. An additional 20 mg of AIBN was added along with 120 μL of poly(ethylene glycol) methacrylate (PEGMA) and stirred for 40 min.
[0281] Experiment 4
[0282] Methyl methacrylate (12 mL) was added dropwise to deionized water (64 mL) at 70 °C and emulsified in the presence of inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 10 min. An additional 20 mg of AIBN was added along with 120 μL of poly(ethylene glycol) dimethacrylate (PEGDMA) and stirred for 40 min.
[0283] [ka] PEGDMA
[0284] Experiment 5
[0285] Methyl methacrylate (12 mL) was added to deionized water (64 mL) at 70 °C and emulsified under the presence of inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 10 min. An additional 20 mg of AIBN was added along with 1.2 mL of poly(ethylene glycol) dimethacrylate (PEGDMA) and stirred for 40 min.
[0286] Test 6
[0287] A solution of sodium dodecyl sulfate (SDS) (0.5 g) in hydroxyethyl methacrylate (HEMA) (15 g) was prepared. This solution was transferred to a round-bottom flask containing deionized water (185 g) in a hot bath set at 70 °C and stirred at high speed. The heat was removed and AIBN (0.2 g) was added while the solution continued to stir.
[0288] Test 7
[0289] A flask containing 64 mL of deionized water was degassed and heated to 70° C. with stirring at 670 rpm for 20 minutes. In the next step, 1 g of stearyl methacrylate was dissolved in 9 mL of methyl methacrylate. This solution was added dropwise to the water over a period of 15 minutes with constant stirring in the presence of inert gas. After addition, ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (40 mg) was added to the emulsion and the mixture / solution was stirred for an additional hour.
[0290] [ka] Stearyl Methacrylate
[0291] Test 8
[0292] A flask containing 64 mL of deionized water was degassed and heated to 70° C. while stirring the contents at 670 rpm for 20 minutes. Separately, 5 g of stearyl methacrylate was then dissolved in 5 mL of methyl methacrylate. This solution was added dropwise to the flask over a period of 15 minutes with constant stirring in the presence of inert gas. After addition, ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (40 mg) was added to the emulsion and stirred for an additional hour.
[0293] Test 9
[0294] A flask containing 64 mL of deionized water was degassed and heated to 70° C. while stirring the contents at 670 rpm for 20 minutes. Next, 5 g of methacrylic acid was dissolved in 5 mL of methyl methacrylate. This solution was added dropwise to the water over 15 minutes with constant stirring in the presence of inert gas. After addition, ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (40 mg) was added to the emulsion and stirred for an additional hour.
[0295] [ka] Methacrylic acid
[0296] Test 10
[0297] A flask containing 64 mL of deionized water was degassed and heated to 70° C. while stirring the contents at 670 rpm for 20 minutes. Next, 1 mL of methacrylic acid was mixed into 5 mL of methyl methacrylate. This solution was added dropwise to the water over 15 minutes with constant stirring in the presence of inert gas. After addition, ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (40 mg) was added to the emulsion and stirred for an additional hour.
[0298] Test 11
[0299] Methyl methacrylate (12 mL) was added dropwise to deionized water (64 mL) at 70° C. and emulsified under the presence of inert gas. The polymerization reaction was catalyzed with ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 5 min. An additional 500 μL of glycidyl methacrylate (GMA) was added and stirred under inert gas for 40 min.
[0300] Test 12
[0301] Glycidyl methacrylate (12 mL) was added dropwise to deionized water (64 mL) at 70° C. and emulsified under inert gas. The polymerization reaction was catalyzed by ((2,2-azobis)2-methyl-propionamidine) dihydrochloride (AIBN) (20 mg) and stirred for 40 min.
[0302] Example 9 - Coating commercially available microparticles with a commercially available emulsion
[0303] The aim of this study is to coat commercially available PMMA particles as cores with a shell comprising susceptors and / or activators via a simple coating method.
[0304] Experiment 1
[0305] In this experiment, 250 mg of PMMA (Soken MX-500ML) was added to 50 mL of water in a beaker. It was then sonicated in an ultrasonic disintegrator for 30 min at 20% amplitude. At the same time, a commercial CNT dispersed in polyurethane (SP-05032022-3) was diluted 100 times and added to another beaker. The PMMA and water dispersion was kept stirred at room temperature to avoid precipitation of PMMA particles. Then, 10 ml of CNTs dispersed in polyurethane was added dropwise to the PMMA dispersion at 0.5 ml / min using a syringe pump. The sample was left overnight to allow the coated PMMA particles to settle. The particles were then separated using a centrifuge.
[0306] Experiment 2
[0307] In this experiment, 250 mg of PMMA (Soken MX-500ML) was added to 50 mL of water in a beaker. It was then sonicated in an ultrasonic disintegrator for 30 minutes at 20% amplitude. At the same time, a commercial epoxy-CNT (SP-05032022-05) was diluted 100 times and added to another beaker. The PMMA and water dispersion was kept stirring at room temperature to avoid the precipitation of PMMA particles. Then, 10 ml of the diluted epoxy-CNT was added dropwise to the PMMA dispersion at 0.5 ml / min using a syringe pump. The sample was left overnight to allow the coated PMMA particles to settle. The particles were then separated using a centrifuge.
[0308] Experiment 3
[0309] In this experiment, 250 mg of PMMA (Soken MX-500ML) was added to 50 mL of water in a beaker. It was then sonicated in an ultrasonic disintegrator for 30 min at 20% amplitude. At the same time, a commercial CNT dispersed in polyurethane (SP-05032022-3) was diluted 10 times and added to another beaker. The PMMA and water dispersion was kept stirred at room temperature to avoid precipitation of PMMA particles. Then, 10 ml of CNTs dispersed in polyurethane was added dropwise to the PMMA dispersion at 0.5 ml / min using a syringe pump. The sample was left overnight to allow the coated PMMA particles to settle. The particles were then separated using a centrifuge.
[0310] Example 10 - Method for using carbon nanostructures as susceptors
[0311] This work shows that the use of commercially available carbon nanostructures as radio frequency (RF) radiation susceptors within matrix particles can aid in the release of catalysts to initiate polymerization reactions. For example, heating the susceptor melts the particle's matrix, releasing chemical components such as copper salt catalysts that initiate polymerization. The goal of this work is to use commercially available PMMA particles as carriers for copper activators.
[0312] The particles produced in the experiments in this study were prepared by using commercially available particles with micro- to nano-scale diameters as carriers for the acrylic surfactants, and attaching the surfactants to the surface of the matrix particle core.
[0313] The microparticles from Experiment 6 above were used in the following heating time course measurements.
[0314] Experiment 1
[0315] The microparticles from Run 6 were taken and placed into an acrylic monomer formulation at 0.10 g in 3 g monomer consisting of 3 parts triacrylate monomer (OTA480), 1 part multifunctional acrylic monomer (EBECRYL® 896), 1 part polyurethane-acrylate (EBECRYL® 8811), all from Allnex, and 5000 ppm 4-methoxyphenol (MEHQ), 2% cumyl hydroperoxide (CHP), and 2% 4,N,N-trimethylaniline (DMPT). The data from the heating experiment are shown below in Table 4.
[0316] [Table 3]
[0317] Example 11 - Stability evaluation of particle cores prepared using CNS susceptors
[0318] Study using foam
[0319] The foam cure test was performed by cutting two foams into 4" x 4" cubes. The sample from run 6 of Example 9 above to be tested was pipetted onto one of the foams to evenly cover one side of the cube and make the layer thick enough to stick over the foam pores. The second cube was placed on top of the first cube to completely cover the sample. The foam cube was placed between the two slides with a spacer and even pressure was maintained by fastening the glass slides with a rubber band. The fastened sample was placed in a microwave chamber under a temperature camera. To isolate the sample from direct heating, the sample was placed on an insulator in the microwave chamber. The sample was heated in a microwave oven for a preset time with a power of 800W. After removing the sample from the microwave oven, the setup was carefully disassembled. To test if the foam was bonded together, the corners of the foam were gently pulled apart.
[0320] Type of foam to be tested
[0321] 1 / 2 inch Airtex high density foam (used to make camper cushions, boat seats, chair pads, garden benches, and small foam cushions).
[0322] 1 / 8" divinylmat and 1 / 2" vinyl foam (Frequently used as a core material in composite laminate construction. Adds strength, stiffness, and insulation without adding weight. Foams generally conform easily to shape and bond within layers to create thickness.
[0323] Nomex honeycomb made from aramid fibers. (Honeycomb exhibits excellent flame retardant properties.)
[0324] Study conducted using composite
[0325] Bare-shaped silicone molds were used to evaluate the cure of the bulk composite. One 5cc volume bare mold was filled at a time and placed in the center of the microwave oven under the thermal camera. Only one sample was placed at a time, ensuring that the sample was under the field of view of the thermal camera. The bare mold was heated in the microwave oven at 800W power for a preset time, removed from the microwave oven and inspected to see if any viscosity change or cure had occurred.
[0326] Test sample
[0327] 1. Sample A: Acrylic adhesive formulation without activator (see Example 9, Experiment 1 for formulation details) 2. Sample B: Acrylic adhesive formulation + copper activator 3. Sample C: Acrylic adhesive formulation + matrix particles (containing both susceptor and copper activator)
[0328] Results of experiments performed at room temperature using Airtex foam
[0329] 1. Sample A: Did not cure after 1 month (this sample has no activator). 2. Sample B: Hardened in 30 minutes. 3. Sample C: Hardened within 30 seconds in the microwave, but did not harden even after one month at room temperature.
[0330] Results of experiments conducted at room temperature using divinyl mat, vinyl foam, and honeycomb
[0331] 1. Sample A: Did not cure after 1 month (this sample has no activator). 2. Sample B: Hardened in 30 minutes. 3. Sample C: Hardened within 30 seconds in the microwave, but did not harden even after one month at room temperature.
[0332] Results of experiments carried out at room temperature using composites
[0333] 1. Sample A: Did not cure after 1 month (this sample has no activator). 2. Sample B: Hardened in 30 minutes. 3. Sample C: Cured within 20 seconds in the microwave, but did not cure even after one month at room temperature.
[0334] This experimentally demonstrates how long the effectiveness of the matrix particles of the present invention continues while still providing hardening as needed.
Claims
1. A matrix particle, (i) at least one matrix material; (ii) at least one susceptor element; and (iii) at least one releasable and / or activatable component incorporated into at least one matrix material and adjacent to the susceptor element; Consisting of The matrix may fully or partially change its physical properties, At least one susceptor element is embedded in at least one matrix material, the at least one susceptor element being capable of being thermally activated via electromagnetic radiation; and At least one releasable and / or activatable component is capable of affecting a chemical reaction in a matrix particle.
2. comprising one or more matrices embedded in discrete regions, the discrete regions having one or more shapes; The discrete regions may comprise coatings or different layers; Each region comprises from about zero to a plurality of susceptors and / or releasable components; and 10. The matrix particle of claim 1, wherein the matrix particle generally has at least one region comprising a susceptor and at least one region containing a releasable component.
3. 10. The matrix particle of claim 1, wherein the matrix particle is derived from and / or comprises organic, inorganic, monomeric, oligomeric, polymeric materials, or combinations thereof.
4. 2. The matrix particle of claim 1, wherein the at least one susceptor is selected from the group consisting of fullerene compounds, graphene, single-walled carbon nanotubes, multi-walled carbon nanotubes, carbon nanofibers, carbon nanotubes, doped carbon nanotubes, carbon sheets, one or more iron metals, one or more oxides of iron metals, SPIONS, one or more non-ferrous metals, one or more oxides of non-ferrous metals, transition metals, transition metal oxides, silicon carbide based materials, boron nitride, and one or more combinations thereof.
5. The matrix particle of claim 4, wherein the size of the susceptor is in the range of about 0.1 nm to about 1000 μm.
6. 5. The matrix particle of claim 4, wherein the susceptor comprises a functionalized susceptor, a non-functionalized susceptor, or both functionalized and non-functionalized susceptors.
7. 10. The matrix particle of claim 1, wherein the susceptor is present at the geometric center of a matrix material that is in direct or indirect contact with the susceptor.
8. 10. The matrix particle of claim 1, wherein the susceptor and / or the releasable component are present in an outer layer of the matrix particle, and the susceptor and the releasable component are in direct or indirect contact.
9. 10. The matrix particle according to claim 1, wherein the matrix particle is partially or totally coated with one or more layers of the deformable material.
10. 10. The matrix particle of claim 1, wherein the matrix particle is partially or totally coated with one or more layers of a deformable material, the one or more layers comprising a susceptor and / or a releasable component.
11. 11. The matrix particle of claim 10, wherein the matrix material does not include a susceptor or a releasable component.
12. 10. The matrix particle of claim 1, wherein the at least one releasable and / or activatable component is a single chemical, a combination of chemicals, an organic chemical, and / or an inorganic chemical.
13. 10. The matrix particle of claim 1, wherein the chemical component comprises one or more catalysts, cocatalysts, co-reactants, oxidizers, reaction inhibitor compounds, accelerators, co-promoters, fuels, explosives, or one or more combinations thereof.
14. 10. The matrix particle of claim 1, which releases the releasable component when the matrix deforms, dissolves, melts, expands, shrinks, ruptures, plasticizes, solvates, is affected by light, or a combination thereof.
15. 2. The matrix particle according to claim 1, wherein the matrix is supported on a support optionally comprising a metal, a ceramic, or a glass.
16. 2. The matrix particle of claim 1, wherein the particle is optionally further chemically surface-modified via one or more chemical reactions comprising a releasable moiety, optionally subsequently surface-modified by forming a coating partially or entirely thereon.
17. 10. The matrix particle of claim 1, which has chemical functionality.
18. 10. The matrix particle of claim 1, wherein the releasable component comprises a chemically functional monomer and the matrix material comprises a polymeric material, and optionally the matrix particle is coated with a polymeric coating.
19. 13. A method for preparing the matrix particles of claim 1, comprising the steps of: (i) emulsion, dispersion, and / or suspension polymerization, or (ii) core-shell polymerization; A method comprising:
20. 13. A method for preparing the matrix particles of claim 1, comprising the steps of: (i) coating polymeric microparticles with a material comprising a susceptor and a releasable component; (ii) encapsulating the microparticles incorporating the susceptors and the releasable components with a monomeric, oligomeric, or polymeric material; and / or (iii) fusing the susceptor and the releasable component; (iv) Encapsulating the susceptors and releasable components within internal pores in the core or external pores on the surface of the porous microspheres. The method comprising:
21. 10. A method for preparing the matrix particles of claim 1, comprising the step of copolymerizing: The process, wherein the step of copolymerizing comprises emulsion polymerization, dispersion polymerization, suspension polymerization, or a combination thereof.
22. 1. A method for affecting a chemical reaction, comprising: (i) providing a bulk reaction mixture; (ii) providing a matrix particle according to claim 1; and (iii) Incorporating matrix particles into the bulk reaction mixture The method comprising:
23. 23. The method of claim 22, (iv) irradiating the bulk reaction mixture at least once with at least one frequency of RF radiation and / or at least one frequency of MW radiation to thermally activate the susceptor elements embedded within the matrix particles.
24. 24. The method of claim 23, wherein the application of RF radiation of at least one frequency and / or MW radiation of at least one frequency is performed periodically, the period being regular or irregular.
25. The method of claim 24, wherein the electromagnetic radiation has a wavelength in the range of about 1 m to 1 mm and a frequency in the range between 50 MHz and 30 GHz.
26. 26. The method of claim 25, wherein the frequency of the electromagnetic radiation is in the range of about 915 MHz to about 2450 MHz.
27. The method of claim 25, wherein the frequency of the electromagnetic radiation is in the range of about 915 MHz to about 2450 MHz and / or the power is in the range of 1 to 10,000 W.
28. The method of claim 25, wherein the electromagnetic radiation is applied for 10 seconds to 60 minutes.
29. 26. The method of claim 25, wherein the reaction is a polymerization reaction.
30. 13. A method for releasing a releasable component from a matrix particle according to claim 1, comprising the steps of: (a) dispersing matrix particles in a bulk reaction mixture; and (b) irradiating the bulk reaction mixture at least once with at least one frequency of RF radiation and / or at least one frequency of MW radiation to thermally activate the susceptor elements embedded within the matrix particles. The method comprising:
31. A bulk reaction mixture comprising: A bulk reaction mixture comprising the matrix particles of claim 1.
32. 32. The bulk reaction mixture of claim 31, further comprising an element that is not affected by RF and / or MW radiation.
33. 10. The matrix particle of claim 1, wherein the one or more variable matrix materials comprise a wax, one or more polymethylmethacrylates (PMMA), styrene, or one or more polymers, or copolymers thereof.
34. 10. The matrix particle of claim 1, wherein the at least one releasable chemical moiety comprises an activator or a catalyst.
35. 2. The matrix particle of claim 1, wherein the catalyst comprises one or more of Cu-acetylacetone, Cu-2-ethylhexanoate, ferrocene, dimethylaminomethylferrocene, or one or more combinations thereof.
36. 26. An article prepared using the method of claim 25.
37. In whole or in part, (i) a polymerizable composition or several polymerizable compositions having at least one chemical property; (ii) reinforced composite articles; (iii) laminate articles; (iv) rigid laminate articles; (v) flexible laminate articles; (vi) a foam; or (vii) Combinations thereof 37. An article prepared as claimed in claim 36, wherein
38. 13. A composition comprising the matrix particles of claim 1, the composition being in whole or in part an adhesive, sealant, coating, paint, ink, plastic, molded plastic, thermoset plastic, molded thermoset plastic, or other polymer forming composition.
39. 2. The matrix particle of claim 1, wherein the releasable and / or activatable component is a catalyst selected from the group consisting of transition metal complexes; transition metal alkoxides; stannous (II) bis(2-ethylhexanoate); carboxylates, alkoxides and complexes of tin, bismuth, zinc, titanium; blocked superacids; dodecylbenzenesulfonic acid; dinonylnaphthalenesulfonic acid; N,N',N'',-tris(dimethylaminopropyl)hexahydrotriazine; organic bases; 1,8-diazabicyclo[5.4.0]undec-7-ene; 1,5-diazabicyclo[4.3.0]nonene-5); (1,4-diazabicyclo2.2.2octane); and combinations thereof.
40. 1. A multi-layer polymer composition comprising:
10. A multilayer polymer composition comprising a first matrix particle of claim 1 and one or more additional matrix particles of claim 1, the additional matrix particles being positioned on the first matrix particles forming one or more matrix particle layers.
Citation Information
Patent Citations
One-package curing adhesive composition and method for bonding therewith
JP1998017836A
Magnetic nanocapsules as thermal latent polymerization catalysts or initiators
JP2019526435A
Inductively curable composition
US20170198116A1
Heating of polymeric materials
US20180148557A1
Curable resin systems and applications thereof
WO1993015131A2